Four Years of Real-Time GRB Followup by BOOTES-1B (2005–2008) - Martin Jelínek; Alberto J. Castro-Tirado; Antonio de Ugarte Postigo; Petr Kubánek; Sergey Guziy; Javier Gorosabel; Ronan Cunniffe; Stanislav Vítek; René Hudec; Victor Reglero; Lola Sabau-Graziati (Advances in Astronomy, 2010)
Four years of BOOTES-1B GRB follow-up history are summarised for the first time in the form of a table. The successfully followed events are described case by case. Further, the data are used to show the GRB trigger rate in Spain on a per-year basis, resulting in an estimate of 18 triggers and about 51 hours of telescope time per year for real-time triggers. These numbers grow to about 22 triggers and 77 hours per year if we include also the GRBs observable within 2 hours after the trigger.